E-Progression of Nonprofit Organization Websites: U.S. Versus Thai Charities. Issue 3 (2nd July 2016) - Kirk, Kristin; Abrahams, Alan; Ractham, Peter
ABSTRACT: Nonprofit organizations are pivotal actors in society, working in various sectors attempting to fill gaps between government services and the market. This interdisciplinary research compared nonprofit websites in Thailand, a developing country, to nonprofit websites in the United States to determine progression through an adapted e-business stage model. A manual decoding process of websites and a web crawling analysis software, Sitebeam, were used to determine the nonprofits' e-progression. Thai and U.S. nonprofits did not differ significantly from each other in terms of presence building content or interactivity, but the U.S. websites were more advanced in e-transactions than the Thai websites (55% vs. 37%). The acceptance of e-transactions was also found to be highly associated with greater online presence and interactivity, suggesting that there is significant room for advancement among organizations that do not accept e-transactions both in Thailand and the United States